Unfit offenders in NSW: paying the price for gaps in service provision. Issue 5 (2nd September 2020) - Eagle, Kerri; Davis, Todd; Ellis, Andrew
Abstract : The Mental Health (Forensic Provisions) Act 1990 (NSW) was amended in 2013 to include section 54 A, enabling an application to be made for the extension of a forensic patient's status. Thirteen patients were subject to an extension order between 2014 and 30 June 2018. Shared characteristics of these forensic patients were considered with a view to identifying the types of patients involved in these applications and the gaps in service provision that this might reflect. Nine out of the 13 patients subject to an extension order had a background of sexual offences, and all patients had either an intellectual disability and/or complex comorbid disorders, such as severe personality disorder. The extension orders coincide with gaps in the service provision in relation to the management of certain complex mental disorders, intellectual disability and problematic behaviours that lead to justice system involvement. The authors discuss the potential implications that these findings have for future resource allocation, legislative reform and service provision.